2020
DOI: 10.1021/acs.joc.0c02201
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral gem-Difluoromethylene Compounds by Enantioselective Ethoxycarbonyldifluoromethylation of MBH Fluorides via Silicon-Assisted C–F Bond Activation

Abstract: The enantioselective ethoxycarbonyldifluoromethylation of Morita−Baylis−Hillman (MBH) fluorides with Me 3 SiCF 2 CO 2 Et under organocatalysis is described. Moderately functionalized chiral gem-difluoromethylene compounds with a stereogenic "C-CF 2 -C*" unit were synthesized in high yields with high enantioselectivities. The initial C−F bond activation is assisted by the silicon atom via a dual S N 2′-S N 2′ stepwise pathway. Dynamic kinetic resolution of the MBH-fluorides explained the high yields and high ee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…The configuration of the enantiomer predominantly formed when (DHQD)2PHAL was used as the catalysts was assigned as S based on the analogy with previous reports. [4][5] Similar to the previously reported allylations using allylic fluorides, these reactions also proceed as kinetic resolutions of the starting allylic 6 fluoride. The residual fluorides that could be isolated at the end of the reactions were typically highly enantioenriched.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…The configuration of the enantiomer predominantly formed when (DHQD)2PHAL was used as the catalysts was assigned as S based on the analogy with previous reports. [4][5] Similar to the previously reported allylations using allylic fluorides, these reactions also proceed as kinetic resolutions of the starting allylic 6 fluoride. The residual fluorides that could be isolated at the end of the reactions were typically highly enantioenriched.…”
supporting
confidence: 61%
“…In the arena of C-centered nucleophiles, Shibata's pioneering studies have demonstrated that alkynyl, trifluoromethyl and some benzyl silanes can be used as C-centered pronucleophiles in allylic substitutions of allylic fluorides catalyzed by chiral Lewis bases (Scheme 2). [5] We took advantage of the same approach to achieve enantioselective allylation of silylated difluoromethyl phosphonate and for the first time produced bioisosters of allyl phosphates in an enantioselective manner. [6] Unlike nitrogen centered nucleophiles, the C-H acidic precursors of carbanions are not strongly nucleophilic and they thus avoid the problems outlined above.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, efforts toward the development of efficient methods to access CF 2 -containing molecules have been witnessed over the past decade. 6 However, most of these developed synthesis methods mainly focus on the preparation of difluoroalkylated arenes (ArCF 2 R) with CF 2 at the benzylic position. 6 a ,7…”
Section: Introductionmentioning
confidence: 99%